The role of RIBS on digital transformation and technological changes in the Spanish publishing industry - Magadán Díaz, Marta; Rivas García, Jesús Israel (Malaysian journal of library&information science, 2021)
The present study, employing survey research design, analyzes the role of Knowledge-Intensive Business Services (KIBS) in the processes of digital transformation and technological changes of publishing companies in Spain. The overall objective of this study is to gauge the scope and depth of the impact of KIBS on Spanish publishers; specifically to identify the drivers of this collaboration through the Transaction Costs Theory; and to determine the degree of support in their transition to new business models. An online survey was administered to the 992 publishers belonging to DILVE, the Internet-based platform that facilitates the management and distribution of bibliographic data, and marketing information of books published in Spain. A total of 310 publishing companies responded to the survey questionnaire, giving a response rate of 31.3 percent. Findings suggested that KIBS are not seen as a threat - neither in the evolution and progress of the publishing sector nor in its digital transformation, modernization, and competitive improvement - but as an opportunity instead as KISS allow accessing all those innovations that, otherwise, would be difficult for Spanish publishers to achieve in isolation.
Keywords: knowledge-intensive business services; transaction costs; publishing industry; book publishing; publishing business model; WOS(2); Scopus